2006
DOI: 10.1038/oby.2006.77
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY and Proglucagon mRNA Expression Patterns and Regulation in the Gut

Abstract: YY and proglucagon mRNA expression patterns and regulation in the gut. Obesity. 2006;14:683-689. Objective: Peptide YY (PYY) and glucagon-like peptide-1 are important in the control of energy homeostasis and are both secreted from the gut in response to ingested nutrients. However, more studies are needed on nutrient regulation of their gene expression patterns in specific areas of the gut. This study detailed PYY and proglucagon (the gene that encodes glucagon-like peptide-1) gene expression patterns and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
112
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 30 publications
19
112
1
2
Order By: Relevance
“…These studies would therefore suggest that increasing the intake of fermentable dietary fibres and colonic production of SCFA would stimulate PYY and GLP-1 release. Indeed, a number of studies have reported that animals fed high doses of fermentable fibres have increased endogenous secretions of PYY and GLP-1 (55)(56)(57)(58)(59) , as well as an increased number of colonic L-cells (60) . In human subjects, it has been shown that adding 24 g of the fermentable fibre oligofructose to a test meal significantly increased GLP-1 levels in the postprandial period (61) .…”
Section: Scfa Receptors and Anorectic Gut Hormone Releasementioning
confidence: 99%
“…These studies would therefore suggest that increasing the intake of fermentable dietary fibres and colonic production of SCFA would stimulate PYY and GLP-1 release. Indeed, a number of studies have reported that animals fed high doses of fermentable fibres have increased endogenous secretions of PYY and GLP-1 (55)(56)(57)(58)(59) , as well as an increased number of colonic L-cells (60) . In human subjects, it has been shown that adding 24 g of the fermentable fibre oligofructose to a test meal significantly increased GLP-1 levels in the postprandial period (61) .…”
Section: Scfa Receptors and Anorectic Gut Hormone Releasementioning
confidence: 99%
“…Moreover, both GLP-1 and leptin are implicated in the pathogenesis of obesity and diabetes. Butyrate directly increases peptide YY/proglucagon gene expression in vitro (199) . Such a result is observed in vivo in RS-fed rats.…”
Section: In Pathological Conditionsmentioning
confidence: 99%
“…The up-regulated expression of GLP1 and GIP at the jejunal mucosa of pigs fed the EMS diet might have therefore indicated greater jejunal glucose and SCFA concentrations compared with pigs fed the CON diet. Both incretins are potent antihyperglycemic hormones, inducing glucose-dependent stimulation of insulin secretion while suppressing glucagon secretion (Zhou et al, 2006;Den Besten et al, 2015b). Serum glucose was similar among pigs at the time of sampling.…”
Section: Discussionmentioning
confidence: 93%
“…In both studies, elevated SCFA concentrations either in colonic or cecal digesta could explain the up-regulation of MCT1 expression (Woodward et al, 2012;Haenen et al, 2013). Glucose and luminal SCFA induce expression of GLP1 and GIP in L-and K-cells of the intestinal mucosa (Zhou et al, 2006;Nøhr et al, 2013;Pluske, 2013). The up-regulated expression of GLP1 and GIP at the jejunal mucosa of pigs fed the EMS diet might have therefore indicated greater jejunal glucose and SCFA concentrations compared with pigs fed the CON diet.…”
Section: Discussionmentioning
confidence: 97%